Pengembangan Media Buku Bergambar CATEBA Untuk Melatih Kemampuan Keaksaraan Anak Kelompok B - Rabiatul Adwiyah; Gunawan Gunawan; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2022)
This study aims to produce an appropriate CATEBA picture book media, so that it can be used in learning activities to train the literacy skills of group B children. This study uses the Research and Development (R&D) method with the ADDIE model or Analysis, Design, Development, Implementation, and Evaluation. The product developed is CATEBA picture book media (Find, Paste, Read) with play activities to find letters, paste letters, and read which have been assessed and validated by media validators, material validators, and school teachers. The data collection technique used observation, documentation, and validation sheet questionnaires. The research instrument was in the form of a validation questionnaire by experts. The data obtained were analyzed using a qualitative descriptive method. The results showed that the CATEBA picture book produced based on the results of the expert's assessment obtained the "very feasible" criteria in all aspects. It can be concluded that the CATEBA picture book is very suitable to be used as a medium in learning activities to train the literacy skills of group B children.